Hiding information by using Discrete Laguerre Wavelet Transform with new algorithms (Journal of the College of Basic Education, 2022)
In this work, the focus was on embedding images and hiding image information in another image by mixing the two images analyzes using the new Discrete Laguerre Wavelets Transform (DLWT) by Approximate and Details coefficients. This method is used for the first time in this field to embedding two images and hide submerged image features. The results were compared with other waveforms indicating that the new wavelet transform proved efficient during the application of two simple examples, including immersing two mysterious images, the other example being the mask and the face.